Polymer-functionalized nanoparticles: from stealth viruses to biocompatible quantum dots. (December 2009) - Jia, H; Titmuss, S
In this article, we focus on nanoparticles that have been functionalized by polymers. We draw our examples from nanoparticle systems that have found biomedical and therapeutic applications. Our aim is to highlight the physical principles that might explain why these systems have been found to be successful in biomedical applications and to highlight other physical properties that might lead to new applications. We consider viruses, gold nanoparticles, magnetic nanoparticles and quantum dots, focussing attention on the ways in which functionalization by polymers has been used to alter the physical characteristics of the particular nanoparticle to improve its function as a possible therapy. In the case of viral vectors, polymer functionalization tunes the biocompatibility, suppressing the binding of antibodies and conferring the nanoparticle with stealth properties. By contrast, the inorganic nanoparticles comprise materials in a form that is not normally encountered in the human body, and polymer functionalization is necessary to ensure biocompatibility.